The legal concept of work-related injury and disease in Australian OHS and workers’ compensation systems - Clayton, Alan; Johnstone, Richard; Sceats, Sonya (Canberra, 2002)
"This paper analyses the concept of ‘work-relatedness’ in Australian workers’ compensation and occupational health and safety (OHS) systems. The concept of work-relatedness is important because it is a crucial element circumscribing the limits of the protection afforded to workers under the preventative OHS statutes, and is a threshold element which has to be satisfied before an injured or ill worker can recover statutory compensation. While the preventive and compensatory regimes do draw on some similar concepts of work-relatedness, as this paper will illustrate, there are significant differences both between, and within, these regimes. This paper offers a comparative survey of the statutory legal concept of work-related injury and disease across all ten workers’ compensation and OHS jurisdictions. The notion of ‘work-relatedness’ is central to the boundary-setting task of workers’ compensation systems in particular, but also has some importance in OHS schemes. However, as will be explored in the next section, the notion of work-relatedness, and in particular the manner in which this concept has been utilised – either explicitly or implicitly – as a control device in setting system boundaries and mandating threshold requirements for entitlement or system coverage, is one that varies according to context and time. Particularly in the workers’ compensation context, this variation represents the playing out of political and economic struggles and their reflection in the balance between the broadening of entitlement (both in terms of access to, and level of, compensation benefits) on the one hand and scheme affordability (in terms of the level of employer premiums) on the other. In the OHS statutes, there has been a significant expansion in regulatory reach, but the precise scope of these developments, and the concepts upon which they have been built, have varied from jurisdiction to jurisdiction. The paper begins with an overview of the evolution of the different conceptions of work-relatedness in the Australian workers’ compensation context, and is followed by a more detailed analysis of the different dimensions of work-relatedness in current Australian workers’ compensation statutes. Many of these dimensions are also present in the evolution of the notion of work-relatedness in the OHS statutes, as will be explored in the latter part of this paper. Throughout the paper the analysis of the notion work-relatedness in the workers’ compensation and OHS statutes will be located within seven conceptions of work-relatedness which are outlined in the following section."